From Vulnerability to Resilience: Hans-Georg Bohle's Scholarship and Contemporary Political Ecology - Watts, Michael J. (DIE ERDE – Journal of the Geographical Society of Berlin, 2016)
My emphasize on Bohle’s distinctive approach to vulnerability is related to the arc of my broad concern in this contribution, namely how vulnerability has since his writings on the topic in the early 1990s has become attached to three other keywords – or concepts – in novel ways that dominate both current analytical and prescriptive work across many domains from global poverty to conflict to urban governance to global pandemics and financial crashes: namely security, resilience and risk. Take for example, the new book by the President of the Rockefeller Foundation, Judith Rodin, entitled The Resilience Dividend. She has, according to the blurb on the back cover, recalibrated the foundation to address the disruptions, shocks and stresses associated with our interconnected world. In this age of complexity says Rodin, the ability to quickly and effectively bounce back is an urgent social and economic issue. The five characteristics of resilience (2015:14) – awareness, diversity, integration, self-regulation and adaptiveness – provide the building blocks of the “adaptive cycle” - a four-phase model integrating the ideas of Brian Holling (“resilience”), Jay Forrester (“systems thinking”) and Joseph Schumpeter (“creative destruction”). Rodin is of course not alone. In our times, resiliency has become a keyword (Williams 1985) for understanding the challenges of inhabiting, and living with the consequences of the Anthropocene (Schoon 2006). In this sense one might say that resiliency (along with its siblings security, and risk) has become a powerful technology of contemporary governance and neoliberal rule. Building resilient persons, communities and institutions is the sine qua non of twenty-first century forms of liberalism. Resilience provides an indispensable road-map by which all of us are purportedly able to anticipate and tolerate the disturbances, dangers and radical contingencies of inhabiting a complex world in which, to again quote the President of the Rockefeller Foundation in its new resilience manifesto, “we cannot predict where the next major shock to our well-being will manifest” (Rockefeller Foundation 2013:1). The argument I want to make is that in incorporating vulnerability into what is now a rather major academic industry operating under the sign of socio-ecological complexity, resilience thinking and risk management, much of the critical edge – the dialectical quality – of Bohle’s work has been lost. My focus will be on issues of food, famine and climate – topics of great interest to Hans-Georg and indeed on which he published extensively – and what resilience theory may, or may not, have to offer in light of the vulnerability analyses of the sort developed by Bohle and others.